Evolution of University - Implications for Education - Malewski, Mieczysław (INSTED: Interdisciplinary Studies in Education & Society, 1998)
In this article the author approaches university as an educational organisation and follows the results of its changing features and their impact on the educational processes. In the author?s opinion university, which was first a community of people searching for the truth, has taken the character of a market oriented enterprise. It tries to equip its graduates in technological professional skills. In the level of aims, university gave up wisdom to replace it with efficiency. This is accompanied by spreading the idea propagated by university - of continuous education. It legitimates the present change and fulfils important marketing functions for university.